An Unreported Uterine Rupture in an Unscarred Uterus After Induced Labor With 25 μg Misoprostol Vaginally - Eva Rydahl; Jette Aaroe Clausen (Elsevier, 2014)
Uterine rupture without a former history of cesarean delivery or uterine scarring is an exceedingly rare complication in pregnancy and labor. Misoprostol is widely used to induce labor but there is a lack of knowledge about serious adverse effects. It is especially challenging to collect reports on side effects because misoprostol is not a registered drug. We report a case of a woman induced by one dose 25 μg misoprostol vaginally. Her pregnancy was uncomplicated and she had an unscarred uterus. Her labor progressed rapidly and she experienced hyperstimulation, meconium stained amniotic fluid, uterine rupture, and excessive blood loss of approximately 14 l. The child survived but is diagnosed with cerebral palsy. The case was never reported as an adverse event. This case questions the safety of misoprostol even in low dosage. It also underlines the need to report side effects to national reporting systems.